Analyzing Grammatical Error Patterns in English Foreign Language Students - Dela Wahyuni; Afzylianur Harahap; Dea Saharani; Rosa Anjani; Siti Ismahani (Jurnal Pendidikan dan Sastra Inggris, 2024)
study explores grammatical errors found in descriptive essays written by five English major students at a university in Medan using a qualitative approach. The students produced texts freely, and their writing was analyzed to identify recurring error patterns and the factors that triggered them. Results show that the most common errors relate to verb agreement, tense use, sentence structure, and linking words, mostly influenced by Indonesian language interference and limited exposure to English writing. These mistakes also reflect low self-monitoring habits during the writing process. Rather than indicating failure, errors demonstrate developmental progress and the learners’ attempt to construct meaning in a second language. The study suggests contextual grammar teaching supported by writing practice, authentic input, and constructive feedback. With consistent guidance, students are expected to gradually build grammatical accuracy in academic writing.